Validation of the Spanish Childhood Trauma Questionnaire-Short Form in adolescents with suicide attempts - García-Fernández, Ainoa; Martínez-Cao, Clara; Sánchez-Fernández-Quejo, Alberto; Bobes-Bascarán, Teresa; Andreo-Jover, Jorge; Ayad-Ahmed, Wala; Cebriá, Ana Isabel; Díaz-Marsá, Marina; Garrido-Torres, Nathalia; Gómez, Sandra; González-Pinto, Ana; Grande, Iria; et al. (Frontiers in Psychology, 2024)
Background: Child maltreatment is associated with a higher probability of mental disorders and suicidal behavior in adolescence. Therefore, accurate psychometric instruments are essential to assess this. Objective: To validate the Spanish version of the Childhood Trauma Questionnaire-Short Form (CTQ-SF) in adolescents with suicide attempts. Methods: Multisite cohort study of 208 adolescents with suicide attempts using data from the following scales: Mini International Neuropsychiatric Interview (MINI), Columbia Suicide Severity Rating Scale (C-SSRS), Patient Health Questionnaire (PHQ-9), and CTQ-SF. Statistical analysis: CTQ-SF scores analyzed by descriptive statistics. Internal consistency: McDonald’s omega and Cronbach's alpha. Concurrent validity with PHQ-9 and C-SSRS scores: Spearman correlation coefficient. Structural validity: Confirmatory factor analysis. Results: Floor and ceiling effects: Physical abuse and neglect as well as sexual abuse demonstrated high floor effects (50.0, 35.1, and 61.1% of adolescents, respectively). No ceiling effects were found. The CTQ-SF had excellent internal consistency (McDonald’s omega=0.94), as did the majority of its subscales (Cronbach's alpha 0.925- 0.831) except for physical neglect (0.624). Its concurrent validity was modest, and the emotional neglect subscale had the lowest Spearman correlation coefficients (0.067- 0.244). Confirmatory factor analysis: Compared with alternative factor structures, the original CTQ-SF model (correlated 5-factor) exhibited a better fit [S-B χ2=676.653, p<0; RMSEA (90% CI=0.076-0.097)= 0.087; SRMR=0.078; CFI=0.980; TLI=0.978]. Conclusions: The Spanish CTQ-SF is a reliable, valid instrument for assessing traumatic experiences in adolescents at high risk of suicide. It appears appropriate for use in routine clinical practice to monitor maltreatment in this group.